Professional Development ‒ Perspective of Business English Teachers in Vocational High Schools in Serbia - Vidaković, Mirna M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
This paper addresses professional development of teachers who run Business English courses in vocational high schools in Serbia. The analysis of professional development programmes offered in Serbia indicated that Business English teachers’ needs are not sufficiently met. Therefore, by investigating teachers’ attitudes, experience, and needs with regard to professional development, it is possible to gain valuable guidelines which might help improve the overall situation. The research, which was of both quantitative and qualitative nature, was conducted with 31 respondents who were asked to complete the questionnaire which centred on the topics such as frequency of attending professional development (PD) programmes, criteria for selecting them, types of PD activities that teachers undertake, attitudes towards features of PD programmes such as quality, relevance, applicability, etc., teachers’ needs in terms of strengthening various professional competences (e.g. field competences, curricular competences, ICT competences, etc.), ways of improving professional development programmes and the like. The teachers’ responses confirmed that the current situation regarding professional development in Serbia is unfavourable, but also reflected their understanding and awareness of the importance of this process for building their professional identity and improving their pedagogical practices. The respondents expressed a high level of need for developing both general and specific teaching competences. They also highlighted the importance of being provided with contemporary, relevant and applicable programmes which are delivered by educators who are well acquainted with both pedagogical theory and teachers’ working environment. Taking into account teachers’ needs while choosing the location and determining the time of PD activities could additionally increase PD attendance. Another factor that could improve the overall situation regarding professional development is the greater presence of virtual PD programmes.